2011
DOI: 10.1021/ol200420u
|View full text |Cite
|
Sign up to set email alerts
|

Tirandamycins from Streptomyces sp. 17944 Inhibiting the Parasite Brugia malayi Asparagine tRNA Synthetase

Abstract: Lymphatic filariasis is caused by the parasitic nematodes Brugia malayi and Wuchereria bancrofti and asparaginyl-tRNA synthetase (AsnRS) is considered an excellent antifilarial target. The discovery of three new tirandamycins (TAMs), TAM E (1), F (2), and G (3), along with TAM A (4) and B (5), from Streptomyces sp. 17944 was reported. Remarkably, 5 selectively inhibits the B. malayi AsnRS and efficiently kills the adult B. malayi parasite, representing a new lead scaffold to discover and develop antifilarial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 22 publications
3
79
0
Order By: Relevance
“…Three tirandamycins isolated from Streptomyces sp. 17944 inhibited the parasitic nematode Brugia malayi at 30 μM concentrations (Yu et al 2011). The antibiotics affected the Asparagine tRNA synthetase, which suggests that the mechanism of action in E. histolytica could be through affecting RNA associated enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Three tirandamycins isolated from Streptomyces sp. 17944 inhibited the parasitic nematode Brugia malayi at 30 μM concentrations (Yu et al 2011). The antibiotics affected the Asparagine tRNA synthetase, which suggests that the mechanism of action in E. histolytica could be through affecting RNA associated enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…CB01883 selected based on the chemical profiling during fermentation optimization. The new compounds feature varying modifications at the A-ring (1-6), B-ring (7) and C-ring (8)(9)(10), expanding the structural diversity of the IFQ and IIQ family of natural products. Antibacterial assays have showed that 11 and 1, 5-7 exerted moderate and weak activity, respectively, against several Gram-positive bacteria tested.…”
Section: Antibacterial Activitiesmentioning
confidence: 99%
“…The NPLI biases natural products from Actinomycetales that are isolated from unexplored or underexplored ecological niches and unavailable in public strain collections. [7][8][9][10][11][12][13][14][15][16][17] The current library at TSRI consists of (i) purified natural products with fully assigned structures, (ii) C-18 mediumpressure liquid chromatography fractions, and (iii) crude extracts of microbial fermentation. Typically, strains were fermented in multiple media and subjected to HPLC and LC-MS analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the laboratories of Shen and Ju discovered more tirandamycin derivatives (tirandamycin F–J) from Streptomyces sp. 17944 14,15 and Streptomyces sp. SCSIO 1666.…”
mentioning
confidence: 99%